GE_GERICHTE A/4008/2006 vom 30. November 2006 - GE Cour de justice (2006)
Représentation professionnelle, exécution d'une séquestre | LP.27.1, LP.49, LP.274, OPC.1, OPC.2, LaLP.13.2, CC.554, CC.538, CPS.169